2007
DOI: 10.1515/sg-2007-0031
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Male Reproductive Success in a Cryptomeria japonica Seed Orchard Revealed by Microsatellite Marker Analysis

Abstract: We investigated the influence of male flower production, floral synchrony and inter-tree distances on male reproductive success in a miniature seed orchard of Cryptomeria japonica. We used six microsatellite markers to determine the paternity of each seed. In the seed orchard, the average pollen contamination and clonal self-fertilization rates were 38.7 % and 1.7 %, respectively. The level of male reproductive success of constituent clones varied from 0.0 to 15.7 %. Five clones showing the highest male reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
2
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
7
2
1
Order By: Relevance
“…In addition, Fernandes et al (2008), in a study performed in a P. pinaster CSO, concluded that the probability that a seed embryo sampled from a mother tree was derived from an outcrossing event was 90.1±2.3%. The absence of selfing found in our study was not surprising in spite of the selffertilization rates of around 5% found in most seed orchards examined to date (Moriguchi et al 2007). In fact, many of the seeds and seedlings produced by inbreeding have a lower viability than outcrossed individuals, so that the inbreds often remain undetected because of large-scale early mortality (Linhart 2000).…”
Section: Discussioncontrasting
confidence: 42%
“…In addition, Fernandes et al (2008), in a study performed in a P. pinaster CSO, concluded that the probability that a seed embryo sampled from a mother tree was derived from an outcrossing event was 90.1±2.3%. The absence of selfing found in our study was not surprising in spite of the selffertilization rates of around 5% found in most seed orchards examined to date (Moriguchi et al 2007). In fact, many of the seeds and seedlings produced by inbreeding have a lower viability than outcrossed individuals, so that the inbreds often remain undetected because of large-scale early mortality (Linhart 2000).…”
Section: Discussioncontrasting
confidence: 42%
“…Bigger trees may indeed exhibit higher flowering intensity resulting in higher attractiveness to the pollinator or higher fertilisation probability for wind-pollinated species. A few studies support this hypothesis: male flower production had a strong effect on male reproductive success (Cryptomeria japonica, Moriguchi et al 2007;Sorbus torminalis, Oddou-Muratorio et al 2005) or on flower visitation (in the herbaceous plant Silene latifolia, Shykoff and Bucheli 1995). However, we do not know whether d.b.h and flowering intensity are strongly correlated in P. avium.…”
Section: Unequal Paternity Contributions and Reproductive Successmentioning
confidence: 91%
“…Moriguchi et al (2007) investigated the influence of floral synchrony on paternity contribution in Cryptomeria japonica, but did not find any significant effect in a pollen shedding period of 1.5 months (Moriguchi et al, 2005), and thereby considerably longer than in A. nordmanniana. Like us, Moriguchi et al (2007) found a significant relationship between male strobili production and male reproductive success, but their linear regression model only explained around 15% of the variation in siring success. In Pinus thunbergii, Goto et al (2005) also found a significant association between male fecundity and male reproductive success -their regression model explained around 43% of the variance -again with a non-significant effect of floral synchrony.…”
Section: Value Of Male Strobili Scoring To Predict Paternal Contributmentioning
confidence: 93%